Characteristic analysis of pantograph–catenary detachment arc based on double‐pantograph–catenary dynamics in electrified railways. Issue 4 (18th August 2022) - Zhou, Hongyi; Liu, Zhigang; Xiong, Jiaming; Duan, Fuchuan
Abstract: With the increase of train speed in electrified railways, the increasingly violent interaction of pantograph–catenary (PC) makes the PC detachment arc an extrusive phenomenon, especially in the double‐pantograph–catenary (DPC) system. Despite a large number of research studies have focussed on the PC arc in a single pantograph system, the studies of PC arc in the DPC system are relatively insufficient. In this paper, the arcing phenomenon in the DPC system is studied by combining it with DPC dynamics. First, through analysing the PC interaction in the double pantograph coupled model, the contact force and vertical displacement of PC are obtained, which are used to analyse the detachment state and fit the detachment trajectory. Then, a dynamic PC detachment arc model is established by extending the black‐box arc model and introducing the detachment trajectory. Next, a circuit model of CRH380BL electric multiple units (EMUs) with a DPC system is established to simulate the dynamic arc model. Finally, the characteristics of arc and their coupling transient influences are analysed under different initial design parameters of the DPC system and the correlation of arc characteristic and arc influence is discussed. The validity of the DPC arc model is verified by experiment results.